Implementasi Metode Qawaid dan Terjemah Dalam Pembelajaran Maharah Qira’ah Santri Pondok Pesantren Tarbiyatul Qur’an (TQ) Darussalam Talang Watuagung Prigen - Ahmad Arif Romadhoni,; Syarifuddin; Syaifullah (Mu'allim, 2023)
reading skill (maharatul qiro'ah) is a skill that is quite difficult to learn, because it requires the discipline of Arabic grammar, mufradat and being able to understand the meaning of the text being read. Darussalam Talang Watuagung prigen Pasuruan Tarbiyatul Qur'an (TQ) Islamic boarding school is one of the Islamic boarding schools that applies the Qawaid and Translation methods in Maharah Qira'ah learning. for this reason researchers feel it is important to conduct research with the aim of describing the implementation of the maharotul qiro'ah method and the supporting factors and obstacles to implementation at the Tarbiyatul Qur'an Islamic Boarding SchoolThis research uses descriptive qualitative research with research instruments using case studies. The population in this study were all TQ Islamic Boarding School students. The results of this study indicate that the grammar and translation methods applied at TQ Darussalam Islamic Boarding School in improving reading skills have 3 namely 1. Isti'dadiyah (preparation) phase, 2. Implementation phase, and 3. Evaluation phase, all of which students must pass gradually . while the factors that support the enthusiasm of the students in participating in reading skills learning grammar and translation methods include demands for an increase in the level of education implemented at the Darussalam Islamic Boarding School and demands for formal education that require them to be able to understand Arabic texts. Factors inhibiting the application of Grammar and Translation methods in learning Reading Skills include: limited learning media, limited learning time and no repetition of learning material